Mediating role of socio-religious behavior on consumption pattern changes of middle-class Muslims: An analysis using SEM - Syaparuddin Razak; Irwan Abdullah; Jumriani Raking; Andi Nuzul (Cogent Business & Management)
This study aims to investigate the mediating effect of socio-religious behavior on consumption pattern changes of middle-class Muslims in the new normal era. In terms of methodology, this study is a correlational survey research. Research data were collected through questionnaires as many as 553 middle-class Muslim respondents who live in South Sulawesi Province, Indonesia. Reliability was accepted with cronbach’s alpha coefficient, and validity was accepted by confirmatory factor analysis. Data analysis and hypothesis testing were carried out through structural equation modeling and multiple regression. Two softwares (SPSS and LISREL) were used for statistical data processing. The results of the study indicate that the full mediation of socio-religious behavior was found in the relationship between religiosity, attitude, and consumption pattern changes, while in the relationship of subjective norms, perceived behavioral control and consumption pattern changes, socio-religious behavior was found as a partial mediation. In other words, the model proposed to form a fundamental change in consumption patterns of the middle-class Muslims does not work optimally. However, this study still finds an important thing that socio-religious behavior is able to mediate the relationship between religiosity, attitude, and consumption pattern changes.